THE CORRELATION BETWEEN BURNOUT SYNDROME AND TENSION-TYPE HEADACHE IN NURSES AT THE ROEMANI MUHAMMADIYAH HOSPITAL SEMARANG - Zafirah, Adela; Prihatin, Murwani Yekti; Setiawan, Muhammad Riza (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2025)
Tension-type headache (TTH) is the most common form of primary headache in the general population, with a one-year prevalence ranging from 38 to 78%. The most common triggers for TTH are stress and emotional conflict. Nurses are among the workers exposed to high work stressors, placing them at risk of developing TTH, which is often triggered by chronic occupational stress known as burnout syndrome. This study aims to determine the correlation between burnout syndrome and tension-type headaches in nurses. This research employed an observational cross-sectional design conducted on 87 nurses at Roemani Muhammadiyah Hospital in Semarang, using proportional random sampling. The research instruments included a tension-type headache questionnaire and the Maslach Burnout Inventory (MBI). The statistical test used is the chi-square test. Among the 87 respondents, mild burnout syndrome was present in 64.4%, moderate burnout syndrome in 24.1%, and severe burnout syndrome in 11.5%. Respondents reporting tension-type headache constituted 26.4%, compared to 73.6% without this condition. The majority of respondents with severe burnout syndrome also experienced tension-type headaches (70%). There was a significant correlation between burnout syndrome and tension-type headaches among nurses at Roemani Muhammadiyah Hospital, Semarang, with a p-value of less than 0.005. Keywords: burnout syndrome, headache, tension-type headache DOI : 10.35990/mk.v8n4.p355-365